The Role of Workload, Environment, and Career Advancement in Shaping Job Satisfaction - Fajar, Muhammad Luthfan; Kurniawati, Desi Tri (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to analyze the effects of workload, workplace environment, and career development on employee job satisfaction at PT Pejaten Jaya Abadi. Design/Methodology/Approach – This study employs a quantitative research approach. Data were collected through questionnaires distributed to 120 employees of PT Pejaten Jaya Abadi. The data were analyzed using multiple linear regression with IBM SPSS version 30 to examine the relationships between workload, workplace environment, career development, and job satisfaction. Findings – The results indicate that workload has a significant negative effect on employee job satisfaction, while workplace environment and career development have significant positive effects on job satisfaction. Among the examined variables, workplace environment has the strongest influence on employee job satisfaction. The coefficient of determination value of 79.9% indicates that workload, workplace environment, and career development explain most of the variation in employee job satisfaction. These findings suggest that organizations should manage workload effectively, establish a supportive workplace environment, and strengthen career development programs to improve employee satisfaction. Originality/Value: This research provides value by simultaneously examining workload, workplace environment, and career development within a single integrated model, offering a comprehensive view that is still limited in prior studies. The findings contribute original empirical evidence from a real organizational setting, strengthening both theoretical insight and managerial implications. Purpose – This study aims to analyze the effects of workload, workplace environment, and career development on employee job satisfaction at PT Pejaten Jaya Abadi. Design/Methodology/Approach – This study employs a quantitative research approach. Data were collected through questionnaires distributed to 120 employees of PT Pejaten Jaya Abadi. The data were analyzed using multiple linear regression with IBM SPSS version 30 to examine the relationships between workload, workplace environment, career development, and job satisfaction. Findings – The results indicate that workload has a significant negative effect on employee job satisfaction, while workplace environment and career development have significant positive effects on job satisfaction. Among the examined variables, workplace environment has the strongest influence on employee job satisfaction. The coefficient of determination value of 79.9% indicates that workload, workplace environment, and career development explain most of the variation in employee job satisfaction. These findings suggest that organizations should manage workload effectively, establish a supportive workplace environment, and strengthen career development programs to improve employee satisfaction. Originality/Value: This research provides value by simultaneously examining workload, workplace environment, and career development within a single integrated model, offering a comprehensive view that is still limited in prior studies. The findings contribute original empirical evidence from a real organizational setting, strengthening both theoretical insight and managerial implications.